Design development practices of selected local retail companies of ready-to-wear apparel - Tejada, Joy Tarina J.; Escano, Maria Monica R. (2005.)
At point-of sale, the customers' attention is drawn to the aesthetic appeal of a particular style. Design development is the process of creating new styles for an apparel line (Frings, 1999). It involves research on fashion trends, color, and fabric and trim; the conceptualization of a design idea; and style selection (Burns, 1997). The general objective of the study was to determine how selected local retailers of ready-to-wear apparel develop product design. The literature is significant to the local garment industry, specifically in the area of design development. It is also useful to potential entrepreneurs in the ready-to-wear apparel industry. Students taking courses related to clothing can also use the research in their respective subjects, especially those in design, merchandising, and production. The paper is baseline in the area of study and may be useful to future researches similar or related to it. The study covered selected local retail companies of ready-to-wear apparel operating in the Philippines. Their design development practices were the scope of the study. Development of actual samples was not part of the research. This is a descriptive study on the design development practices of selected local retail companies of ready-to-wear apparel. Purposive sampling was used to select the respondents. The study targeted 13 respondents, however, only 4 companies agreed to take part in the study due to confidentiality of data. The research was conducted with the aid of interviews and observation, and use of secondary research materials. The research used content analysis to organize and analyze the data gathered. Examination of the frequencies of the responses made by the respondents, combined with the analysis of previously researched literature was also done. Tables and figures were used to present the data in an organized manner. The process of design development differs from one respondent to the next. However, results show that researching fashion trends as the first step is the common factor for all companies. Essentially, design development undergoes research, formulation of a design concept, actual designing of the apparel line, and approval. Design is one of the greatest assets that the clothing industry has and the major reason why consumers buy new clothing. Although the companies in the study know the factors that influence design, some of them lack a coherent strategy for this aspect of product development.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Retail trade; Clothing trade -- Philippines